Characteristics of ambitious entrepreneurs in Southeast Europe region: High-growth expectation concept - Miodrag Petrović; Bojan Leković (Anali Ekonomskog fakulteta u Subotici, 2020)
The main objective of this paper is to determine the factors of influence on high-growth expectations in order to determine the characteristics of these entrepreneurs in SEE region. For the purpose of this research, data from the Global Entrepreneurship Monitor was used. For the purpose of this research, the authors included six countries in research sample of South East Europe: Slovenia, Croatia, Hungary, Romania, Bosnia and Herzegovina, and FYR of Macedonia. An exploratory sample of the mentioned countries was 12027 respondents and 231 entrepreneurs with high-growth expectations. Data analysis was made through the SPSS program for statistical analysis. Nature of the observed variables has conditioned usage of Logistic regression. Our findings demonstrate that entrepreneurial motives, entrepreneurial KSA's, innovation and internationalization activity have a positive relationship with high-growth expectations.